The gendered consequences of the COVID‐19 lockdown on unpaid work in Swiss dual earner couples with children. Issue 6 (18th June 2022) - Steinmetz, Stephanie; Vandecasteele, Leen; Lebert, Florence; Voorpostel, Marieke; Lipps, Oliver
Abstract: This article assesses the gendered impact of COVID‐19 measures on changes in time that Swiss dual earner couples spent on unpaid work during the pandemic, focusing on families with children. Overcoming some of the methodological shortcomings of previous studies, high‐quality representative panel data allow us to examine the change in time invested in housework and childcare before and during the pandemic, and test theoretical assumptions as to the mechanisms underlying the observed patterns. Gender inequalities are explained by the couple's work division prior to, and at the onset of, the pandemic and interpreted in the light of key theoretical approaches (economics of the family, bargaining and time availability, doing gender). Our results imply that in particular changes in the time availability of the partner are relevant for changes in time spent on housework, while in case of care work, the own time availability matters more. Moreover, we also found that the respondents' economic bargaining power within the couple matters both for housework and care work. Finally, the implemented COVID‐19 measures neither led to an increase in patriarchal power structures nor did they foster an increase in equality for unpaid work among women and men. Instead, the results show that changes in time availability due to short‐time, remote or overtime working schemes determined changes in time spent on unpaid care to a larger extent than gender alone.